The impacts of selective logging on non-timber forest products of livelihood importance - Rist, L.; Shanley, P.; Sunderland, Terry C.H.; Sheil, Douglas; Ndoye, O.; Liswanti, N.; Tieguhong, J.C. (2011)
The potential for combining timber and non-timber forest product extraction has been examined in the context of diversified forest management. Many tropical forests are exploited both commercially for timber and by forest-dependent communities for non-timber forest products (NTFPs). Divergences between these two uses may have significant implications for forest-dependent livelihoods. This article gathers existing examples of conflicts and complementarities between selective logging and non-timber uses of forest from the livelihood perspective. Additionally it draws on three case studies from Brazil, Cameroon and Indonesia to examine by what mechanisms, and to what extent, logging impacts forest resources of livelihood importance, as well as to consider how factors such as logging regime and forest management system may mediate such influences. By doing so we aim to shed further light on a relatively unacknowledged issue in tropical forest management and conservation. Four specific mechanisms were identified; conflict of use and the indirect impacts of logging being those most commonly implicated in negative effects on livelihood-relevant NTFPs. Eighty two percent of reviewed articles highlighted negative impacts on NTFP availability. Examples of positive impacts were restricted to light demanding species that respond to the opening of forest structure and typically represent a small subset of those of livelihood value. Despite considerable impacts on livelihoods, in all three case studies we found evidence to support the potential for enhanced compatibility between timber extraction and the subsistence use of NTFPs. Drawing on this evidence, and findings from our review, we make specific recommendations for research, policy and management implementation. These findings have significant implications for reconciling timber and non-timber uses of tropical forests.